Characterization Of SiO2/SiC Interface Of Phosphorous-Doped MOS Capacitors By Conductance Measurements - Idris, Muhammad Idzdihar; Mohammed Napiah, Zul Atfyi Fauzan; Zainudin, Muhammad Noorazlan Shah; Mohd Chachuli, Siti Amaniah; Rashid, Marzaini (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Interface states of MOS structures capacitors incorporated with low levels of phosphorous have been investigated by conductance and C-ψs method. The frequency response of interface states was observed by the conductance method up to 10 MHz. The correlation between the frequency response of interface states and interface state density determined by C-ψs method was studied. It was found that fast states in phosphorous incorporated samples reduced significantly at high frequency (>5 MHz) while sample annealed with nitrogen remained high up to 10 MHz. The interface state density, Dit of phosphorous incorporated sample near conduction band is lower compared to nitridated sample. These results indicate phosphorous passivation effectively reduces Dit at the SiO2/SiC interfaces and can be correlated to high channel mobility.